Al-Rasyidin's Perspective Of Islamic Education - Junaidi Arsyad; Azizah Hanum OK; Miswanto Miswanto (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims: 1) to describe the biography and biography of Al Rashidin, 2) to analyze Al Rashidin's thoughts on Islamic education, and 3) to analyze the relevance of Al Rashidin's Islamic education to contemporary education. This study uses a qualitative descriptive approach, where descriptive research is not intended to test certain hypotheses, but only describes what it is about a variable, symptom, or situation. The type of research used is library research or library research. The data collection technique used in this research is the documentation method. The results showed that: 1) Al Rasyidin was born in Sinaksak Village, Tapian Dolok BatNanggar District, Simalungun Regency, North Sumatra Province, on January 20, 1967. Books: Philosophy of Science in Islamic Tardis, Philosophy of Islamic Education, Ontology Framework Building, Epistemology, and Axiology of Islamic Educational Practices, Sparks of Educational Thought From Philosophy to Educational Practices, etc. 2) Al Rashidin's thoughts on Islamic education, namely Al Rashidin defines Islamic education based on three concepts of understanding different terms, namely tarbiyah, ta'lim, and ta'dib. The purpose of Islamic education according to Al Rasyidin, is to develop physical and spiritual potential, where the development of physical potential aims to develop and actualize the physical potential of students. 3) The relevance of Al Rasyidin's Islamic education perspective with contemporary education is the perspective of Islamic boarding schools, madrasas, and integrated madrasas. Government policies that are relevant to the perspective of Al Rasyidin's Islamic education are the goals of national education and the profile of Pancasila students.